Prevalence of minimal hepatic encephalopathy in cirrhotic patients - Héctor Jesús Maldonado-Garza (Annals of Hepatology, 2011)
Background. Minimal hepatic encephalopathy (MHE) has implications for health-related quality of life as well as for survival of cirrhotic patients, but a standardized diagnostic test is not available.Objective. To determine the prevalence of MHE among cirrhotic patients by using the psychometric hepatic encephalopathy score (PHES) system and the critical flicker frequency (CFF) test to diagnose MHE and to identify factors that influence the results of these tests.Material and methods. From April 2007 to March 2008, PHES and CFF tests were performed on patients with cirrhosis but no overt hepatic encephalopathy. Descriptive statistics were used to express the results and the Spearman correlation was used to evaluate CFF and PHES results according to age and education level.Results. We studied 104 patients. The prevalence of MHE was 55.8% (n = 58) based on a positive result for either the PHES or the CFF test, 32.7% (n = 34) based on positive PHES results alone, 34.6% (n = 36) based on positive CFF test results alone and 11.5% (n = 12) based on a positive result for both tests. According to PHES, the incidence of MHE was correlated with education level (r = 0.333, p = 0.001), but not with age. According to CFF, the incidence of MHE was correlated with age (r = -0.93, p = 0.049), but not with education level.Conclusion. The prevalence of MHE was similar to that previously reported. Patient literacy influences MHE diagnosis with PHES but not with CFF. CFF is a simple and feasible method that identifies patients with MHE who may benefit from treatment independently of their education level.